A review on The Malaysian Public Private Partnership (PPP) - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Aripin, Srazali; Ahmad Sarkawi, Azila (2016)
The paper provides a review on the Malaysian Public Private Partnership (PPP). Through a desk study, the paper begins by defining the key concept of PPP and presents the evolution of the Malaysian PPP and its implementation. Moving on, the paper provides a detailed analysis of PPP projects implementation in Malaysia and highlights key issues and problems